Identification of Favorable Zones of Gas Accumulation via Fault Distribution and Sedimentary Facies: Insights From Hangjinqi Area, Northern Ordos Basin - Anees, Aqsa; Zhang, Hucai; Ashraf, Umar; Wang, Ren; Liu, Kai; Mangi, Hassan Nasir; Jiang, Ren; Zhang, Xiaonan; Liu, Qi; Tan, Shucheng; Shi, Wanzhong (Frontiers in Earth Science, 2022)
The Hangjinqi area was explored for natural gas around 40 years ago, but the efficient consideration in this area was started around a decade ago for pure gas exploration. Many wells have been drilled, yet the Hangjinqi area remains an exploration area, and the potential zones are still unclear. The Lower Shihezi Formation is a proven reservoir in the northern Ordos Basin. This study focuses on the second and third members of the Lower Shihezi Formation to understand the controlling factors of faults and sedimentary facies distribution, aimed to identify the favorable zones of gas accumulation within the Hangjinqi area. The research is conducted on a regional level by incorporating the 3D seismic grid of about 2500 km2, 62 well logs, and several cores using seismic stratigraphy, geological modeling, seismic attribute analysis, and well logging for the delineation of gas accumulation zones. The integrated results of structural maps, thickness maps, sand-ratio maps, and root mean square map showed that the northwestern region was uplifted compared to the southern part. The natural gas accumulated in southern zones was migrated through Porjianghaizi fault towards the northern region. Well J45 from the north zone and J77 from the south zone were chosen to compare the favorable zones of pure gas accumulation, proving that J45 lie in the pure gas zone compared to J77. Based on the faults and sedimentary facies distribution research, we suggest that the favorable zones of gas accumulation lie towards the northern region within the Hangjinqi area.